Combinatorial phenotypic screen uncovers unrecognized family of extended thiourea inhibitors with copper-dependent anti-staphylococcal activity. Issue 4 (3rd March 2016) - Dalecki, Alex G.; Malalasekera, Aruni P.; Schaaf, Kaitlyn; Kutsch, Olaf; Bossmann, Stefan H.; Wolschendorf, Frank
Abstract : We have exploited the natural antibacterial properties of copper ions for the discovery of novel metallo-antibiotics to target drug resistant bacteria. Abstract : The continuous rise of multi-drug resistant pathogenic bacteria has become a significant challenge for the health care system. In particular, novel drugs to treat infections of methicillin-resistant Staphylococcus aureus strains (MRSA) are needed, but traditional drug discovery campaigns have largely failed to deliver clinically suitable antibiotics. More than simply new drugs, new drug discovery approaches are needed to combat bacterial resistance. The recently described phenomenon of copper-dependent inhibitors has galvanized research exploring the use of metal-coordinating molecules to harness copper's natural antibacterial properties for therapeutic purposes. Here, we describe the results of the first concerted screening effort to identify copper-dependent inhibitors of Staphylococcus aureus . A standard library of 10 000 compounds was assayed for anti-staphylococcal activity, with hits defined as those compounds with a strict copper-dependent inhibitory activity. A total of 53 copper-dependent hit molecules were uncovered, similar to the copper independent hit rate of a traditionally executed campaign conducted in parallel on the same library. Most prominent was a hit family with an extended thiourea core structure, termed the NNSN motif. This motif resulted in copper-dependent and copper-specific S. aureus inhibition, while simultaneously being well tolerated by eukaryotic cells. Importantly, we could demonstrate that copper binding by the NNSN motif is highly unusual and likely responsible for the promising biological qualities of these compounds. A subsequent chemoinformatic meta-analysis of the ChEMBL chemical database confirmed the NNSNs as an unrecognized staphylococcal inhibitor, despite the family's presence in many chemical screening libraries. Thus, our copper-biased screen has proven able to discover inhibitors within previously screened libraries, offering a mechanism to reinvigorate exhausted molecular collections.